ANALISIS PRINSIP KESATRIAAN DALAM PENGGUNAAN KILLER ROBOT DALAM KONFLIK BERSENJATA - Mahmood Faiz Baraja; Jun Justinar (Fakultas Hukum Universitas Trisakti, 2021)
The change in terms from the Law of Armed Conflicts to International Humanitarian Law is avery important point of development. In its arrangement, the humanitarian aspects are essentialto safeguard and protect civilians and hors de combat combatants. Humanitarian law has thePrinciple of Chivalry in it, which states that honesty in war must be upheld. However, with thedevelopment of the times and technology, it also develops for weapons of war. The mostadvanced progress of weapons of war is the autonomous weapon system. The issue at hand iswhether the usage of autonomous weapons systems disregards the chivalry principles ofinternational humanitarian law? This paper will answer the subject by comparing the prohibitionof other weapons on the basis that it is not in line with the principle of chivalry, and by consideringand comparing the views of officials on this matter.